Papillon-Lefevre Syndrome - L. Izakovičová Hollá; A. Fassmann; M. Kukletová; V. Sazmová (Czech Dental Chamber, 2009)
Papillon-Lefevre syndrome (PLS) is a rare autosomal recessive disorder characterized by severe early-onset periodontal destruction involving both the deciduous and permanent dentition and skin lesions of palmoplantar hyperkeratosis. Recently it was found that PLS patients carry loss-of-function mutations in the gene encoding cathepsin C (CTSC). The aim of this study was analyzed the CTST gene in one Czech family with PLS. Peripheral blood samples were obtained from individuals belonging to this family for DNA isolation. Mutations were identified by direct sequencing of genomic DNA amplified for selected regions of the cathepsin C gene. 12-old year patient and his grandfather had a classic PLS phenotype. We analyzed all exons of the CTSC gene and identified a mutation in intron 1 (rs217077). Both affected individuals were homozygous for T allele; our child's mother and unaffected brother carried a heterozygote combination of this mutation. Dipeptidyl-peptidase I encoded by the CTSC gene play an immune and inflammatory role. Many different mutations in this gene have been reported in patients with PLS from several ethnic groups. This is the first genetic study of Papillon-Lefevre syndrome in the Czech population.